The Legality of Transmigrant Land Evictions from a Constitutional Law Perspective - Agung Mubarak; Multi Sri Asnani; Dirawati (Ekasakti Journal of Law and Justice, 2026)
The transmigration program is a strategic instrument of the state within the Welfare State framework that aims to equalize development and the welfare of the people. However, in its implementation, agrarian conflicts often occur in the form of evictions of transmigrant land for infrastructure development or other strategic projects. The problem becomes complex when the government unilaterally categorizes uncertified transmigration land as free state land, thereby ignoring the constitutional rights of citizens. The purpose of this study is to analyze the legal status and constitutional guarantees for transmigrant land and to test the legality of these evictions in terms of the principles of the rule of law and the General Principles of Good Governance (AAUPB). The research method used is normative juridical with a statutory approach and a conceptual approach. The results of the study indicate that transmigrant land rights are a manifestation of Article 28H paragraph (4) and Article 33 paragraph (3) of the 1945 Constitution, which have the status of vested rights (rights that have been born) since the legal placement by the state was carried out. The absence of a land ownership certificate is not a legal basis for evictions, but rather a form of maladministration and state negligence in carrying out the certification mandate as mandated by the Transmigration Law. The unilateral eviction of the land has been proven to violate the principles of accuracy and legal certainty in the AAUPB and indicates an abuse of authority (detournement de pouvoir). The conclusion of this study emphasizes that the government is obliged to carry out collective certification progressively and prioritize equal deliberation to ensure legal certainty and the dignity of the Indonesian rule of law